DEVELOPMENT OF SHARED-TYPE INTEGRATED E-MODULE WITH THEME â€œMOTION OF OBJECTS AND LIVING THINGS IN OUR ENVIRONMENTâ€ FOR SECONDARY SCHOOL SCIENCE LESSON - Yusri, Hilman; Sari, Monica Prima (Universe, 2023)
This study aims to develop a shared-type integrated e-module with theme â€œMotion of objects and living things in our environmentâ€ for secondary school science lesson. Plomp model is used in this Research and Development study, which consist of three stages namely: preliminary research, prototype stage, and assessment stage. A set of questionnaires was prepared to test validity and practicality of product. Validity test was conducted involving three lecturers from Science Education department, and practicality test was conducted involving 9 students and 3 science teachers at SMPN 1 Kampar. The results of the validity test gave the value of 89.79% which belongs to highly valid category, practicality test with students gave the value of 90.74% and with teacher 93.75% which belong to highly practical.